Theoretical bases of qualitative research in accounting sciences - Alegre Brítez, Miguel Ángel (2021)
The qualitative approach in the investigations of the Accounting Sciences is based on a research process that allows achieving results that are different from those of the quantitative method. The research’s general objective was to describe the main characteristics of the qualitative research’s theoretical bases in accounting sciences. A documentary analysis of 20 scientific articles of referents in the accounting sciences on qualitative research was carried out. The results were processed through Atlas. You. and shown in a narrative and conceptual form. The main results were: 1) There are various possibilities to carry out a qualitative research and 2) The qualitative approach of the investigations allows to be more open, to solve problems that could not be addressed with a different approach, and to question aspects of the quantitative research. The main conclusion was: The results of the qualitative research allow them to be used as a complementary tool to financial statements, as they are a different way of understanding the accounting process.